Waiting time and idle time of uncertain queueing system. Issue 8 (17th November 2021) - Liu, Yang; Liu, Baoding
Abstract : Uncertain queueing system is a waiting line in which the interarrival times and service times are both modeled by uncertain variables. This paper investigates four important performance characteristics of uncertain queueing system, including waiting time, idle time, total idle time and total busy time. The analytical formulas of uncertainty distributions of those performance characteristics are also derived separately.